Effect of storage temperature with vacuum packaging on physicochemical stability of Ulva ohnoi - Wiraz Wicaksana Azwar Naval; Ramadhan Wahyu; Dyah Hardiningtyas Safrina; Fariz Pari Rizfi; Uju (BIO Web of Conferences)
Indonesia's seaweed industry, despite its vast potential, predominantly exports raw materials, with value-added processing limited to certain red and brown seaweeds. Green seaweeds, such as Ulva, are largely untapped by the processing industry despite their abundance and potential natural pigment sources. Ulva undergoes rapid color deterioration in tropical climates, indicating pigment degradation and quality loss. This study investigated the impact of storage conditions at 4°C (chilling) and 28°C (room temperature) using minimal processing vacuum packaging on the stability of physicochemical properties, color profile, pigment concentration, and antioxidant activity over three months. Results showed that chilling with minimal processing significantly inhibits color degradation and maintains greenness a* value of the start of -15,76±1,11 to -10.91±1,14 while the room temperature is -5.68±0.72. In the third month, chilled samples exhibited significantly higher concentrations of chlorophyll a at 5.71±0.50 μg/mL, in contrast to room temperature, which was 3.83±0.4 μg/mL. Antioxidant activity decreased in the third month. Furthermore, the moisture content in the chilled samples was lower and stable at 28.87±0.16%, compared to samples stored at room temperature, which measured 33.34±0.54%. Chilling temperature with vacuum packaging effectively preserves the quality of Ulva ohnoi, making it suitable for industrial applications. This study provides important insights for storage conditions and increasing the commercial potential of this underutilized seaweed.